New Leadership Models for the Digital and Entrepreneurial Society – Recovering from COVID-19 in an Increasingly Digital Economy - Stoian, Marta (Proceedings of the ... International Conference on Business Excellence, 2023)
Leadership for the digital and entrepreneurial society is a relatively new and emerging area of study, as the rapid pace of technological change has brought new challenges and opportunities for leaders. Forasmuch as digital society continues to evolve and grow, and as COVID-19 has had a significant impact on leadership practices and has brought about some notable changes in how leaders approach their roles, new leadership models are emerging to meet the unique provocations and chances of this context. The scientific literature on this specific topic is still emerging, but some key themes have already come up emphasizing the importance of agility and adaptability as organizations have to rapidly pivot their operations in response to the increasingly necessary digital expansion accelerated by the pandemic. As traditional business models are disrupted, leaders who are able to effectively leverage new technologies while thinking creatively and taking risks are more likely to succeed. Therefore, considering that the subject is still in its early stages, the research topic is to examine the leadership models that should be utilized in order to improve the digital and entrepreneurial context answering the main research questions related to the steps and leadership practices that will make a significant difference in both digital and entrepreneurial societies. The past literature on empirical and theoretical topics is compiled via a systematic review. An analysis of the content that is qualitative and descriptive was planned. Scopus, Web of Science or Google Scholar search results were of great help in carrying out the study and various leadership models were examined. The paper’s theoretical contribution is the definition of a set of rules and criteria on where to focus on leadership. The collection of data for new performance, ownership, efficiency, and business value generation indicators is promoted at all levels.